Overview of human 20 alpha-hydroxysteroid dehydrogenase (AKR1C1): Functions, regulation, and structural insights of inhibitors. (5th January 2022) - Chu, Xianglin; He, Siyu; Liu, Yang; Liu, Yijun; Feng, Feng; Guo, Qinglong; Zhao, Li; Sun, Haopeng
Abstract: Human aldo-keto reductase family 1C1 (AKR1C1) is an important enzyme involved in human hormone metabolism, which is mainly responsible for the metabolism of progesterone in the human body. AKR1C1 is highly expressed and has an important relationship with the occurrence and development of various diseases, especially some cancers related to hormone metabolism. Nowadays, many inhibitors against AKR1C1 have been discovered, including some synthetic compounds and natural products, which have certain inhibitory activity against AKR1C1 at the target level. Here we briefly reviewed the physiological and pathological functions of AKR1C1 and the relationship with the disease, and then summarized the development of AKR1C1 inhibitors, elucidated the interaction between inhibitors and AKR1C1 through molecular docking results and existing co-crystal structures. Finally, we discussed the design ideals of selective AKR1C1 inhibitors from the perspective of AKR1C1 structure, discussed the prospects of AKR1C1 in the treatment of human diseases in terms of biomarkers, pre-receptor regulation and single nucleotide polymorphisms, aiming to provide new ideas for drug research targeting AKR1C1. Highlights: Detailed analysis that the structural features and functions of the AKR1Cs. Detailed analysis that the relationship between AKR1C1 and diseases. Summarize the research progress of AKR1C1 inhibitors. Give insight into the design of AKR1C1 inhibitors for follow-up research. Provide our insights on the prospects of AKR1C1 in disease treatment.